Organic matter composition in coastal sediments at Terra Nova Bay (Ross Sea) during summer 1995 - PUSCEDDU, ANTONIO; DELL'ANNO A.; FABIANO M. (2000)
We illustrate the spatial and vertical distribution of sediment phytopigments and organic matter biochemical composition at Terra Nova Bay (Ross Sea) during summer 1995. Coastal sediments displayed high phytopigments concentrations associated with huge amounts of labile organic matter largely dominated by proteins. This result was opposite to previous observations in the same area. Such comparison suggested that whilst organic matter quantity in the sediments depended upon the vertical input from the water column, temporal changes in its biochemical composition were related to benthic processes. As considerably high concentrations of biopolymeric organic carbon were found even at 6-cm depth and according to the 'loss type' functioning of the coastal waters of the Ross Sea, we stress the summer time occurrence in coastal sediments of an important organic matter burial. 1998). However, the real fate of such organic matter input to the sediments once it enters the benthic trophic chain is still poorly known (Nedwell et al. 1993; Fabiano et al., in press; Danovaro et al., in press). The present paper illustrates the spatial and vertical distribution of sediment phytopigments and organic matter biochemical composition at Terra Nova Bay (Ross Sea), during the early stage of the summer phytoplankton bloom. The aims were to investigate the nutritional value of sediment organic matter by means of its biochemical composition and to furnish further indication on the functioning of the 'loss-type' coastal system of Terra Nova Bay.